Design of miniaturized patch crossover based on superformula slot shapes - Mutaz Akram Banat; Nihad Ibrahim Dib (Institute of Advanced Engineering and Science, 2022)
In this paper, miniaturized microstrip crossover circuits are proposed using slots shapes obtained using the superformula. The design starts by using a conventional half-wavelength square patch crossover. For miniaturization purposes, different superformula slot shapes are introduced on the square patch. The proposed crossovers are designed to operate at 2.4 GHz using a 0.8 mm thick FR-4 substrate with a relative permittivity of 4.4. The designs are simulated using the high frequency structure simulator (HFSS). One of the miniaturized designs is fabricated and its scattering parameters are measured using a vector network analyzer. Simulated and measured results agree very well. At the design frequency, the measured input port matching is better than ˗19 dB, while ????12, ????13 and ????14 have the values of ˗12 dB, ˗2.2 dB and ˗10 dB, respectively. Furthermore, a 71% size reduction is achieved as compared to the conventional crossover area.